Indonesia’s Diplomacy Jihad for Palestine at the United Nations Post-October 2023: A Critical Examination - Fathonah, Bikry; Paramitha, Salsabila Nayla; Pulungan, Fakhrul Haholongan; Muhammadin, Fajri Matahati (Prophetic Law Review, 2026)
Historical ties between Indonesia and Palestine underpin Indonesia's steadfast commitment to supporting Palestine's right to independence. The Al-Aqsa Flood incident on October 7, 2023, followed by Israel’s massive invasion of Palestine, escalated the conflict in Palestine exponentially. This conflict has drawn the attention of the world, including Indonesia, to drastically intensify its diplomacy in supporting Palestine’s independence. Indonesia has undertaken a "Diplomacy Jihad" by actively defending Palestinian rights through various United Nations forums such as the International Telecommunication Union (ITU), the International Court of Justice (ICJ), the UN Human Rights Council (UNHRC), and others. This normative-empirical research critically evaluates the effectiveness of Indonesia’s diplomatic efforts and the obstacles it faces in advocating for Palestinian independence within the UN framework post-October 7, 2023. Our hypothesis is that Indonesia's diplomacy at the UN generally represents an effective form of advocacy in this "Diplomacy Jihad," although critical challenges hinder the potential for an even stronger performance, a trend that is worsening in 2026.